The Effects of Tourism Determinants on Poverty through Economic Growth in Indonesia - Munawwir Abbas; Vivi Silvia; Muhammad Nasir (Graha Primera Saintifika, 2026)
As an archipelagic and developing country, Indonesia faces complex and persistent poverty challenges that hinder both societal welfare and provincial economic growth. This study aims to examine the factors influencing tourism and assess efforts to reduce poverty through economic growth. Using panel data from 34 provinces in Indonesia for the period 2016 to 2024, the analysis applies a random effects regression model. The results show that domestic tourist arrivals, international tourist arrivals, occupancy rates of starred hotels, and occupancy rates of non-starred hotels exert a positive and significant effect on poverty. In contrast, economic growth does not significantly influence poverty and does not function as a mediating variable. To sustain increases in tourist arrivals both domestic and international the government should enhance promotional efforts for Indonesian tourism and strengthen support for regional tourism development. Moreover, providing subsidies and improving access to business loans for hotel operators can help expand their operational capacity. Finally, the government needs to improve the competence of tourism stakeholders through well designed and effective education and training programs.